2012
DOI: 10.1016/j.str.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Intersubunit Interactions in Maintaining SAGA Deubiquitinating Module Structure and Activity

Abstract: Summary The deubiquitinating module (DUBm) of the SAGA coactivator contains the Ubp8 isopeptidase, Sgf11, Sus1 and Sgf73, which form a highly interconnected complex. While Ubp8 contains a canonical USP catalytic domain, it is only active when in complex with the other DUBm subunits. The Sgf11 zinc finger (Sgf11-ZnF) binds near the Ubp8 active site and is essential for full activity, suggesting that the Sgf11-ZnF helps maintain the active conformation of Ubp8. We report structural and solution studies showing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…Accordingly, mutations of Sgf11 ZnF residues that are located at the interface between Ubp8 and Sgf11 ZnF domain impaired Ubp8 activity (5). Moreover, the deletion of Sgf11 ZnF was shown to reduce the Ubp8 enzymatic activity by 2 orders of magnitude, an effect that was correlated to the destabilization of the catalytic site of Ubp8 (32). In addition, the presence of a conserved set of surface-located basic residues in the Sgf11 ZnF suggested that electrostatic interactions with the DNA backbone could be involved in substrate recognition (6).…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, mutations of Sgf11 ZnF residues that are located at the interface between Ubp8 and Sgf11 ZnF domain impaired Ubp8 activity (5). Moreover, the deletion of Sgf11 ZnF was shown to reduce the Ubp8 enzymatic activity by 2 orders of magnitude, an effect that was correlated to the destabilization of the catalytic site of Ubp8 (32). In addition, the presence of a conserved set of surface-located basic residues in the Sgf11 ZnF suggested that electrostatic interactions with the DNA backbone could be involved in substrate recognition (6).…”
Section: Discussionmentioning
confidence: 98%
“…Instead of binding ubiquitin, the ZnF-UBP from Ubp8 functions as an assembly lobe to recruit cofactors, which then stimulate the catalytic activity of its neighboring USP domain (Kohler et al 2010;Samara et al 2010Samara et al , 2012. Analogous to our current examination of Sad1, initial studies of Ubp8 showed that purified full-length Ubp8 did not bind ubiquitin nor did it possess in vitro deubiquitinase activity (Lee et al 2005).…”
Section: Sad1 Protein Does Not Bind Ubiquitin In Vitromentioning
confidence: 70%
“…It was only upon the purification of Ubp8 from cell lysates and the identification of its interacting partners that in vitro deubiquitinase activity could be observed (Ingvarsdottir et al 2005;Lee et al 2005). Finally Ubp8 crystallized in the presence of these factors revealed that they assembled upon the ZnF-UBP domain, which then allowed them to interact with the fingers and catalytic cleft of Ubp8's USP domain to activate USP activity (Kohler et al 2010;Samara et al 2010Samara et al , 2012. Consistent with its ubiquitin-independent function, the ZnF-UBP domain from Ubp8 is missing many of the residues important for ubiquitin recognition ( Fig.…”
Section: Sad1 Protein Does Not Bind Ubiquitin In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of Sgf11-ZnF results in almost loss of Ubp8 catalytic activity since it destabilizes the compact folding of the DUBm (Samara et al, 2010(Samara et al, , 2012.…”
Section: Dubm Function and Structurementioning
confidence: 99%